Suzuki-Kun's mindful life. 1 - Fujimoto, Yuhki (Fujimoto, Yuhki, Suzuki-Kun's mindful life, 2025)
"Looks can be deceiving. After all, one glance at the towering and intimidating Kaoru Suzuki is enough to send people packing...and get others riled up for a fight. But the guy's actually a softie inside, as well as a flower lover and an avid baker, to boot! When Suzuki gets harassed on the train, a delicate but unexpectedly tough boy swoops in to save the day. This unlikely duo kicks off a friendship that proves that what you see isn't always what you get!" --